2007
DOI: 10.48550/arxiv.0706.0792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistence of the 0.7 anomaly of quantum point contacts in high magnetic fields

Abstract: The spin degeneracy of the lowest subband that carries one-dimensional electron transport in quantum point contacts appears to be spontaneously lifted in zero magnetic field due to a phenomenon that is known as the 0.7 anomaly. We measured this energy splitting, and studied how it evolves into a splitting that is the sum of the Zeeman effect and a field-independent exchange contribution when applying a magnetic field. While this exchange contribution shows sample-tosample fluctuations, it is for all QPCs corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Thus, the magnetic field evolution of transmission resonances can be applied to the determination of the g * factor of 1D systems, which is expected to be enhanced by the exchange interaction [2,4]. For our sample we obtained |g * | = 1.2 ± 0.1 (as compared to 0.44 in bulk GaAs), which is in very good agreement with recent data for ballistic QPCs [6]. The advantage of the proposed method is that it can be applied for long, quasi-ballistic quantum wires.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Thus, the magnetic field evolution of transmission resonances can be applied to the determination of the g * factor of 1D systems, which is expected to be enhanced by the exchange interaction [2,4]. For our sample we obtained |g * | = 1.2 ± 0.1 (as compared to 0.44 in bulk GaAs), which is in very good agreement with recent data for ballistic QPCs [6]. The advantage of the proposed method is that it can be applied for long, quasi-ballistic quantum wires.…”
supporting
confidence: 90%
“…The origin of this effect is currently under active debate since this anomaly seems to be an universal, but still unexplained feature of one-dimensional mesoscopic transport. Experimentally, the magnetic field dependence of the additional plateau is common for all studied systems -by applying a parallel in-plane field the 0.7 feature evolves gradually towards 0.5 × 2e 2 /h conductance step, when only one spinpolarised level is occupied [1,2,3,4,5,6]. Therefore, it has been suggested that such an anomalous plateau is due to spontaneous spin polarisation of one-dimensional electron liquid, caused by exchange interactions among carriers in the constricted geometry of the device [2,7].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This analysis points to the conclusion that the spontaneous energy splitting of the 0.7 anomaly is dominated by the same effect that causes the high-field offset ∆E hf o . As we discussed, this is probably an exchange contribution [30]. The error bar that we attribute to these values includes an error from the transconductance peak-fitting, one from the conversion of gate voltage to energy scale, and an error due to scatter in the ∆E datapoints as a function of B.…”
Section: B the 07 Anomaly And Exchangementioning
confidence: 82%